Could it be permissible to prevent the existence of morally enhanced people?. Issue 11 (23rd August 2012) - Persson, Ingmar
Abstract : This paper discusses Nicholas Agar's argument in Humanity's End, that it can be morally permissible for human beings to prevent the coming into existence of morally enhanced people because this can harm the interests of the unenhanced humans. It contends that Agar's argument fails because it overlooks the distinction between morally permissible and morally impermissible harm. It is only if the harm to them would be of the morally impermissible kind that humans are provided with a reason to prevent the coming into existence of enhanced people. But if their enhancement includes moral enhancement, it is unlikely that the enhanced people will cause morally impermissible harm.